Approach to the Twenty First Century: The Ghanaian Ulama Speak Out - Sey, M. (Jurnal Usuluddin, 1997)
The current study attempts to answer the question: What should Muslims in Ghana do in order to progress' In the endeavour to find the answer, prominent Muslim leaders, especially the ulama, were interviewed. These leaders seem to agree that disunity among the Muslims of different tribal background, lack ofproper education which can cultivate Islamic awareness as well as the relevant knowledge and skills suitable for the current situation, lack of proper attitude and skills in organisation management and inadequate and poor management offund tend to hold back the pace of development of the Muslims in Ghana.